Mechanical And Tribological Properties Of Ultra High Molecular Weight Polyethylene With Zinc Oxide Antibacterial Agent For Joint Implant - Chang, Boon Peng (2014)

(untitled)
Total joint replacement (TJR) is a highly successful treatment for end-stage joint disease like osteoarthritis. A prominent number of TJR devices used in orthopaedic involve articulation between a metallic alloy and ultra-high molecular weight polyethylene (UHMWPE). Penggantian sendi keseluruhan (TJR) adalah rawatan yang berjaya untuk peringkat akhir penyakit sendi seperti osteoartritis. Kebanyakan peranti TJR digunakan dalam ortopedik melibatkan artikulasi antara aloi logam dan polietilena berberat molekul sangat tinggi (UHMWPE).